New species of Lopescladius (Cordiella) Coffman et Roback (Chironomidae: Orthocladiinae) from Brazil - Hagenlund, Linn K.; Andersen, Trond; Mendes, Humberto F. (Zootaxa, 2010)
Three new species of Lopescladius (Cordiella) Coffman et Roback, 1984, L. (C.) morosus, L. (C.) vibrissatus and L. (C.) uncatus, from Brazil are described and figured as male imago. An emended generic diagnosis as well as a key to the males are given.